UAV collision avoidance considering no-fly-zones - Lee, Hae-In; Shin, Hyo-Sang; Tsourdos, Antonios (Elsevier, 2021)
This paper proposes a collision avoidance algorithm that ensures minimum separation between the vehicles considering multiple no-fly-zones. The proposed algorithm aims to provide a practical and efficient tactical de-confliction solution for Unmanned Aerial Vehicles (UAVs). The main idea is to utilise the differential geometry concept that computes the minimum heading angle change to avoid the obstacles, and to expand its applicability to polygonal obstacles. This paper validates the minimum separation and efficiency of the proposed algorithm both analytically and numerically
Keywords: Differential Geometry; Unmanned Aerial Vehicle (UAV); Obstacle Avoidance; Collision Avoidance